Development Trends of International Hotel Chains in Uzbekistan (Eurasian Journal of History, Geography and Economics, 2026)
This article examines the current state and development stages of international hotel chains in Uzbekistan. The study analyzes the process of entry and expansion of international hotel brands in the country, their regional distribution, and their concentration in areas with high tourism potential. In addition, the article provides a systematic overview of existing international hotel chains operating in Uzbekistan as well as hotels planned to open in the near future. Special attention is paid to the role of international hotel chains in modernizing the tourism infrastructure, improving service quality, and enhancing Uzbekistan’s competitiveness in the global tourism market. The findings of the study may serve as a valuable reference for tourism professionals and policymakers involved in strategic development planning